Correlation Between Different Molecular Abnormalities of Alpha Thalassaemia Carriers and Their Peripheral Blood Indices - Noor Fadzilah Zulkifli, Dr. (Universiti Sains Islam Malaysia, 2011)
Background: Alpha-thalassemia is an inherited disorder caused by genetic abnormalities. It is characterized by reduced or absent a-globin chains synthesis. Currently, the Ministry of Health is promoting the "Thalassaemia Screening Program". This is because thalassaemia carrier can remain silent without any symptom. However they are at risk of transferring the gene to their offspring and this may create problem if their spouse is also a carrier. This is done based on the initial findings of microcytosis (MCV < 80fl) and hypochromia (MCH <27pg) and confirmed by a molecular study. More than 95% of the cases results from deletion. The common deletions in our region are the Southeast Asian -- SEA, the a-3.7 and a-4.2. To date, there is no study to correlate the red cell indices and the different molecular abnormalities. Therefore, this study is done to see the correlation between different molecular abnormalities in alpha thalassaemia carriers and their peripheral blood indices. Method: This is a retrospective observational study on confirmed alphathalassaemia carriers in 2007 within Kuala Lumpur and Selangor. Results are obtained from Haematology Unit, Institute of Medical Research (IMR). Molecular diagnosis was done by multiplex RT-PCR to look for --SEA, 43.7 -4.2 and - THAI deletions. A statistical correlation of the red cell indices and the different molecular abnormalities was assessed. Results: A total of 118 samples were recruited in the study. However, only 116 cases have a complete full blood count results. Majority of the samples were found to have -SEA deletion (42.4%) followed by heterozygous a-3.7 deletion (38.1%). In cases with heterozygous a-3.7 deletion, majority are Malay (88.89%) followed by Chinese (4.44%), Indian (4.44%) and other ethnic (4.44%). In samples with --SEA deletion, 50% were Chinese, 48% were Malays and the other 2% were Indian. These results are slightly different from the previous study in which most alpha thalassaemia cases are of Chinese ethnicity and majority of the cases with the -SEA deletion was from Chinese ethnic. There is a significant difference in the haemoglobin, MCV and MCH levels between the three groups